2005
DOI: 10.1080/14992020500190201
|View full text |Cite
|
Sign up to set email alerts
|

The effect of impulse noise on distortion product otoacoustic emissions

Abstract: The aim of this study was the evaluation of distortion product otoacoustic emissions (DPOAEs) before and after noise exposure from shooting, and the comparison of DPOAEs with pure-tone audiometry. Thirteen young male police officers were exposed to impulse noise from shooting, without using earplugs. Standard pure-tone audiometry, tympanometry, and DPOAEs were performed before exposure and at one hour post- and 24 hour post-exposure. In the one hour post-exposure testing mean pure-tone thresholds were elevated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 41 publications
3
13
0
1
Order By: Relevance
“…As for the 6kHz, it was the only frequency that showed an amplitude average construed as altered in both groups. Such findings match those of the studies that had recorded that the individuals subjected to noise, even within the thresholds of the normality standard, displayed lesser amplitude in the DPOAEor even the absence of one or more tested frequencies, when compared with the control group 10,11 . The fact that the current research refrains to portray the statistically significant difference when comparing the performance of both groups in the 4kHz frequency in the TEOAE test and in the 6kHz frequency in the DPOAE test, can be justified by the absence of a control group, that is, in this research, both the groups were exposed to noise, in lower or higher levels, that is, both revealed risk factor for hearing loss.…”
Section: Acknowledgementsupporting
confidence: 77%
See 2 more Smart Citations
“…As for the 6kHz, it was the only frequency that showed an amplitude average construed as altered in both groups. Such findings match those of the studies that had recorded that the individuals subjected to noise, even within the thresholds of the normality standard, displayed lesser amplitude in the DPOAEor even the absence of one or more tested frequencies, when compared with the control group 10,11 . The fact that the current research refrains to portray the statistically significant difference when comparing the performance of both groups in the 4kHz frequency in the TEOAE test and in the 6kHz frequency in the DPOAE test, can be justified by the absence of a control group, that is, in this research, both the groups were exposed to noise, in lower or higher levels, that is, both revealed risk factor for hearing loss.…”
Section: Acknowledgementsupporting
confidence: 77%
“…According to the National Committee of Noise and Auditive Preservation 19 , one of the symptoms of hearing loss induced by noise, is the beginning and the predominance 4 in the frequencies of 3, 4 or 6kHz, particularly in the first 10 to 15 years of exposure and, as the lesion worsens, it afterwards Besides, in other studies, the TEOAE and the DPOAE tests proved being more sensitive regarding the identification of cochlear alteration than the tonal liminal audiometry, having the TEOAE revealed greater sensitivity to cochlear changes 5 and the DPOAE allowed the diagnosis of eventual lesion in higher levels, even in individuals with quantitatively normal hearing regarding the tonal audiometry 10,12,13,23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A Greek study consisted of verifying the effect of impact noise on distortion product otoacoustic emissions (DPOAE) in military personnel before and after exposure to firearm noise without ear protective equipment. The conclusion was that DPOAE may provide additional information about cochlear quality that may be used for monitoring purposes because it is a fast, objective, and easily done test 6 . A study of military personnel in the Brazilian navy compared 60 individuals exposed to occupational noise and 60 non-exposed controls by applying TOAE and DPOAE to identify differences.…”
Section: Introductionmentioning
confidence: 99%
“…There are studies on the intensity of firearm noise. A Greek study assessed the sound pressure level caused by military weapons and found sound peaks reaching 160.2 dBSPL 6 . In Brazil, the maximum sound pressure level of firearms used by shooting instructors in the Military Police of Montes Claros, MG, was found to be 108.9 dBSPL 7 .…”
Section: Introductionmentioning
confidence: 99%